I believe in unicorns - Morpurgo, Michael (Oberon plays for young people., 2015)
Tomas loves playing outdoors ' he hates school, books and being dragged to the library by his mother. But his world is turned upside down the day he meets the Unicorn and the Unicorn Lady and is spellbound by their story. Discover the power of storytelling to transform lives as Tomas, with his newfound love of books, becomes instrumental in saving his burning library when his village is devastated by war. We challenge you not to believe in unicorns ' absolutely!